Osteoarthritis year 2013 in review: clinical. - Arden, N; Leyland, K (2013)
Some major themes over the past year in clinical research of osteoarthritis (OA) include obesity, muscle strength, pain mechanisms, novel disease modifying drugs, and risk factors for poor outcomes of joint replacement surgery. A systematic literature search was performed using PubMed from January 2012 to December 2012. The articles selected for this review represent topics the authors thought best highlight recent clinical OA research.